THE EFFECTIVENESS OF E-PORTFOLIO ON STUDENTS' WRITING SKILLS AT SMA NEGERI 21 GOWA - lisa sari; Ariana; Mallombasi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of using e-portfolio, especially Google Sites, in improving students' writing skills, focusing on two main aspects: grammar and organization. This research was conducted at SMA Negeri 21 Gowa using a quantitative approach with a pre-experiment design. A total of 35 students from class XI MIPA 1 were selected as research samples through purposive sampling, considering their relevance and availability for the study. To collect data, students were given writing tests before (pre-test) and after (post-test) the application of e-portfolio. The test was designed to evaluate their writing performance in terms of grammatical accuracy and organization. The students developed and uploaded their writing assignments through Google Sites, which allowed for continuous feedback and revision throughout the learning process. The data collected was then analyzed using Paired Sample T-Test in SPSS to determine if there was a statistically significant difference in students' writing performance before and after the treatment. The findings showed significant improvement in both aspects of writing. The average grammar score increased from 47.14 to 80.71, reflecting an increase of 71.21%, while the organization score increased from 49.28 to 82.14, or an increase of 71.11%. Statistical analysis showed a significance value of 0.000 (p < 0.05), which confirmed the effectiveness of the e-portfolio. These results suggest that integrating digital tools such as Google Sites into writing instruction can foster better learning outcomes, increase student engagement, and encourage greater autonomy in the writing process.